2003
DOI: 10.1161/01.cir.0000050620.37260.75
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor 2–Mediated Vasodilatation in Humans In Vivo

Abstract: Background-Systemic hypotension as a consequence of vascular dysfunction is a well-recognized and important feature of critical illness. Although serine protease activation has been implicated as a cause of vascular dysfunction in systemic inflammation, the mechanism is unknown. Recently, a class of receptors with an entirely novel mechanism of action, protease-activated receptors (PARs), has been identified that would explain the link between protease activation and systemic hypotension. Our aim was to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 41 publications
8
36
1
Order By: Relevance
“…28,29 Although confirming previous observations of PAR-2-mediated venodilatation, 30 we have rather unexpectedly described a dose-dependent venoconstriction with PAR-1 activation. This may be mediated by platelet activation, release of endothelium-derived vasoconstrictors, or a direct effect on venous smooth muscle cells.…”
Section: Venous Effects Of Par-activating Peptidessupporting
confidence: 91%
See 1 more Smart Citation
“…28,29 Although confirming previous observations of PAR-2-mediated venodilatation, 30 we have rather unexpectedly described a dose-dependent venoconstriction with PAR-1 activation. This may be mediated by platelet activation, release of endothelium-derived vasoconstrictors, or a direct effect on venous smooth muscle cells.…”
Section: Venous Effects Of Par-activating Peptidessupporting
confidence: 91%
“…We have not assessed the mechanism of this vasodilatation, but animal and clinical models suggest that this is likely to be endothelium and nitric oxide dependent. 11,30 However, data from animal studies have limited relevance in humans because of the wide species variability in PAR-1 receptor expression and function. The mechanism of PAR-1-induced vasodilatation needs to be addressed in future clinical studies.…”
Section: Arterial Effects Of Par-activating Peptidesmentioning
confidence: 99%
“…22 Other studies have shown that activation of PARs causes vasodilation through a nitric oxide-dependent mechanism. 23 Further studies are needed to define the role of integrins and PARs as possible molecular mechanisms by which elastase could inhibit Ca 2ϩ entry into the smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Protease-activated receptor 2 (PAR2) is expressed on the vascular endothelium, and when it is activated, causes endothelium-dependent vasodilations of a variety of arteries in human and experimental animals via releasing of NO, prostanoids, and endothelium-dependent hyperpolarizing factor (EDHF). [5][6][7] PAR2 is a member of PAR, and it is a class-A G protein-coupled receptor (International Union of Basic and Clinical Pharmacology nomenclature site: http://www.guidetopharmacology.org/nomenclature.jsp). There are four members of the PARs receptor family.…”
Section: Introductionmentioning
confidence: 99%